Adrenomedullin in paraventricular nucleus attenuates adipose afferent reflex and sympathoexcitation via receptors mediated nitric oxide–gamma-aminobutyric acid A type receptor pathway in rats with obesity-related hypertension. Issue 2 (February 2023) - Wang, Fang-Zheng; Qian, Pei; Liu, Mu-Yue; Ding, Lei; Wang, Hong-Yu; Wang, Qian; Ding, Zi-Yang; Jin, Fei-Yu; Li, Rui-Gang; Zhou, Ye-Bo
Abstract : Background: Hypothalamic paraventricular nucleus (PVN) is an important central site for the control of the adipose afferent reflex (AAR) that increases sympathetic outflow and blood pressure in obesity-related hypertension (OH). Method: In this study, we investigated the effects of nitric oxide (NO) and cardiovascular bioactive polypeptide adrenomedullin (ADM) in the PVN on AAR and sympathetic nerve activity (SNA) in OH rats induced by a high-fat diet. Results: The results showed that ADM, total neuronal NO synthase (nNOS) and phosphorylated-nNOS protein expression levels in the PVN of the OH rats were down-regulated compared to the control rats. The enhanced AAR in OH rats was attenuated by PVN acute application of NO donor sodium nitroprusside (SNP), but was strengthened by the nNOS inhibitor nNOS-I, guanylyl cyclase inhibitor (1H-[1, 2, 4]Oxadiazolo[4, 3-a]quinoxalin-1-one, ODQ) and gamma-aminobutyric acid A type receptor (GABAA ) antagonist Bicuculline. Moreover, PVN ADM microinjection not only decreased basal SNA but also attenuated the enhanced AAR in OH rats, which were effectively inhibited by ADM receptor antagonist ADM22–52, nNOS-I, ODQ or Bicuculline pretreatment. Bilateral PVN acute microinjection of ADM also caused greater increases in NO and cyclic guanosine monophosphate (cGMP) levels, and nNOS phosphorylation. Adeno-associated virus vectors encoding ADM (AAV-ADM) transfection in the PVN of OH rats not only decreased the elevated AAR, basal SNA and blood pressure (BP), but also increased the expression and activation of nNOS. Furthermore, AAV-ADM transfection improved vascular remodeling in OH rats. Conclusion: Taken together, our data highlight the roles of ADM in improving sympathetic overactivation, enhanced AAR and hypertension, and its related mechanisms associated with receptors mediated NO–cGMP–GABAA pathway in OH condition.